The potential and possibilities of oral history for skills development at undergraduate level (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Since 2003 the History Department of the University of the Free State (UFS) has been o!ering a third-year module on oral history. From the timeof its inception this module has aimed at providing a balance between oral history theory and methodology, thus enabling students to master and applythe oral history technique in practice. Students are taught how to manage an oral history project from start to finish. The teaching approach is resourcebased with a stronger emphasis on learning than on teaching, which is in line with a current international trend towards constructivism. During the past nine years it has become clear to the authors that apart from the theoretical knowledge gained by the students, various skills are also taught and developed in the practical session of this module. This is clearly revealed when the questionnaires, interviews and student evaluation forms are assessed and analysed. The main purpose of this article is to identify and interpret certain trends and patterns regarding skills development as both a direct and an indirect outcome of this oral history module by using data obtained from the mentioned questionnaires, interviews and evaluation forms. The article addresses certain questions which are crucial for understanding the potential and many possibilities of oral history as a tool for skills development in a transforming society. It is argued that oral history’s potential creates new methodological approaches for developing a diversity of new skills required by a changing social environment. Understanding this potential and its possibilities provides a basis for further developing oral history as a skills development tool, which may also lead to the improvement and expansion ofexisting oral history courses offered at tertiary level
Keywords: Oral history; Constructivism; Teaching and learning; Undergraduate module; Interdisciplinary research